Delay and secrecy: Does industry sponsorship jeopardize disclosure of academic research? - Dirk Czarnitzki; Christoph Grimpe; Andrew A. Toole (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2011)
The viability of modern open science norms and practices depend on public disclosure of new knowledge, methods, and materials. Aggregate data from the OECD show a broad shift in the institutional financing structure that supports academic research from public to private sponsorship. This paper examines the relationship between industry sponsorship and restrictions on disclosure using individual-level data on German academic researchers. Accounting for selfselection into extramural sponsorship, our evidence strongly supports the perspective that industry sponsorship jeopardizes public disclosure of academic research.
urn:nbn:de:bsz:180-madoc-31376
Keywords: O31; O32; L33; 330; Open science; research funding; industry sponsorship; disclosure; secrecy